Cardiac magnetic resonance longitudinal strain analysis in acute ST-segment elevation myocardial infarction: A comparison with speckle-tracking echocardiography. (August 2020) - Valente, Filipa; Gutierrez, Laura; Rodríguez-Eyras, Lucia; Fernandez, Rúben; Montano, Maria; Sao-Aviles, Augusto; Pineda, Victor; Guala, Andrea; Cuéllar, Hug; Evangelista, Arturo; Rodríguez-Palomares, José
Highlights: Speckle-tracking echocardiography is widely used for strain analysis. Magnetic resonance feature tracking was recently developed for strain analysis. Global longitudinal strain shows good correlation between both techniques. Correlation for segmental strain is only moderate and should be used with caution. Feature tracking global and segmental strain shows excellent reproducibility. Abstract: Background: Strain analysis with speckle-tracking echocardiography (STE) is considered superior to ejection fraction for ventricular function assessment in different clinical scenarios. Feature tracking (FT) permits cardiac magnetic resonance (CMR) strain analysis in routinely acquired cine images. This study evaluated the feasibility of CMR-FT and its agreement with STE in patients with acute ST-segment elevation myocardial infarction (STEMI). Methods: An echocardiogram and CMR were performed in 128 patients who underwent primary percutaneous revascularisation after a STEMI. Adequate strain analysis was obtained by both techniques in 98 patients and peak systolic longitudinal strain (LS) was assessed with STE and CMR-FT. Results: Of 1568 myocardial segments, 97.2% were correctly tracked with STE and 97.7% with CMR-FT. For global LS, STE showed a mean of −14.8 ± 3.3% and CMR-FT −13.7 ± 3.0%, with good agreement between modalities [intraclass correlation coefficient (ICC) 0.826; bias −1.09%; limits of agreement (LOA) ± 4.2%]. On the other hand, segmental LS agreement was only moderate, with an ICC of 0.678 (bias −1.14%; LOA ± 11.76%) and the ICC ranged from 0.538 at the basal antero-lateral segment to 0.815 at the apical lateral segment. Finally, both STE and CMR-FT showed excellent intra- and inter-observer reproducibility (ICC > 0.9). Conclusions: CMR-FT provides LS with similar feasibility to STE and both techniques showed good agreement for global LS, although agreement at segmental level was only moderate. CMR-FT showed excellent reproducibility, strengthening its robustness and potential for both research and clinical applications.